2009
DOI: 10.1080/09638190902757368
|View full text |Cite
|
Sign up to set email alerts
|

Trade effects of the Europe agreements: A theory-based gravity approach

Abstract: In this paper, we develop a new version of a theory-based gravity equation to properly account for the relative price indices initially proposed by Anderson and van Wincoop (2003). The partially time-varying character of our multilateral resistance variables overcomes the bias present in earlier studies that solely rely on country or country pair fixed effects. Applying the augmented gravity equation to the process of European Union (EU) integration during the 1990s, we find robust evidence that the Free Trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…romer (1994) demonstrates in a simple calibration that the trade liberalization increases the number of the traded varieties as a source of welfare gains. Spies and Marques (2009) applying the augmented gravity equation find that the free trade agreements between the EU and the cEEcs during the 1990s substantially increased intra-group trade for the czech and Slovak republics and Slovenia at the expense of the rest of the world trade. Bojnec and Fertő (2010) applying the panel regression analysis confirmed that the cEEc agro-food quality differentiation on the EU-15 markets during the pre-accession is explained by comparative advantages from the relative factor endowment.…”
Section: Methodsmentioning
confidence: 99%
“…romer (1994) demonstrates in a simple calibration that the trade liberalization increases the number of the traded varieties as a source of welfare gains. Spies and Marques (2009) applying the augmented gravity equation find that the free trade agreements between the EU and the cEEcs during the 1990s substantially increased intra-group trade for the czech and Slovak republics and Slovenia at the expense of the rest of the world trade. Bojnec and Fertő (2010) applying the panel regression analysis confirmed that the cEEc agro-food quality differentiation on the EU-15 markets during the pre-accession is explained by comparative advantages from the relative factor endowment.…”
Section: Methodsmentioning
confidence: 99%
“…We check the robustness of our baseline results using an approach to multilateral resistance that is derived directly from equation (7), whose denominator term models multilateral trade resistance through all variables that also influence the bilateral resistance to trade, weighted by regional income shares. Since these shares are time-varying, we can overcome the bias present in estimations that solely rely on country (pair) fixed effects to proxy for the multilateral resistance terms (Spies and Marques, 2009). In order to be able to apply standard panel data estimation techniques, the multilateral resistance variables are written as a Taylor series approximation as proposed by Baier and Bergstrand (2009):…”
Section: 3mentioning
confidence: 99%
“…9 The most basic formulation of the gravity model consists of explaining bilateral flows as a direct function of the two partners' economic size (measured in terms of GDP, GDP per capita and/or population) and as an inverse function of the distance between them (Anderson, 2011). In the current paper we propose an extension of the approach taken in Spies and Marques (2009) to incorporate a simplified version of the trade cost function of Novy (2013) and Feenstra and Romalis (2014), who consider two types of trade costs in the context of international trade: the usual "iceberg" _________________________ 7 Some other extra costs arise because the maritime transport mode is slower, and the time loss is sometimes unexpected when the route has to be cancelled due to adverse sea conditions. This time delay may be much more costly for a firm than just the other costs to be paid, but it is hard to place a monetary value on it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the responses by the rest of the world to changes in trade intensity within a preferential trade area. Spies and Marques (2009) build on the model originally proposed by Anderson and Wincoop (2003), but they extend it by developing a wealthier measure of multilateral trade resistance that goes beyond relative prices and covers a wider set of factors affecting trade flows. Empirically, the paper applies the recently developed fixed-effect vector decomposition method (Plu¨mper and Troeger 2007), which corrects for the estimation bias arising from the presence of time-invariant variables in the panel.…”
mentioning
confidence: 99%